Youth Reception of Gender-Based Violence Victim in Soft White Underbelly YouTube Channel - Paulus, Lani Diana; Ningsih, Ida Nuraini Dewi Kodrat; Tanjung, Sumekar (Mediator: Jurnal Komunikasi, 2024)
Soft White Underbelly is a YouTube channel that produces content of interviews with marginalized people in America. It uncovers stories of stigmatized people and reveals the systemic inequality behind their presence. Gender-based violence (GBV) is one of the issues addressed on this channel. It portrays how prostitutes are victims of GBV. The author applied Stuart Hall’s audience reception theory. The theory proposes that media messages are not static. Hall suggested that expectations and prior knowledge influence their text interpretation. This research investigates how young audiences perceive portrayals of GBV victims in Soft White Underbelly's videos on prostitution and explores the factors that influence these perceptions. A qualitative method was adopted, employing audience reception analysis as the approach. Informants were international YouTube users between the ages of 18 and 30. The study finds various receptions, influenced by social factors, media habits, educational levels, personal experiences, and economic factors. Furthermore, this research confirms that Hall's reception theory is evident in today's audience reception. The findings demonstrate how viewers can develop critical awareness, interpret media texts, and disseminate them back into their social environment.